Enhancing prognosis in multiple myeloma bone disease: insights from a retrospective analysis of surgical interventions - Shi, Xiangjun; Yao, Xingchen; Wu, Yue; Du, Boran; Du, Xinru (Frontiers in Surgery, 2024)
BackgroundMultiple myeloma (MM) is a hematological malignancy characterized by bone marrow infiltration and osteolytic tumor formation. Despite advancements in the treatment of this disease, MM remains incurable and often leads to complications, such as multiple myeloma bone disease (MMBD). Surgical intervention is frequently necessary to manage symptoms associated with bone disease, including pain and fractures.MethodsA retrospective review was conducted on 135 patients diagnosed with MMBD who had undergone surgery, compared to 190 patients diagnosed with MM who had not undergone surgery and served as controls. Surgical interventions were performed based on typical clinical presentations of myeloma-related bone disease, as indicated by imaging results. Patients who had only undergone percutaneous kyphoplasty or vertebroplasty (PKP/PVP) were excluded from this study.ResultsAmong patients who underwent surgery, the spine was the most common site of bone metastasis, accounting for 50% of cases. The number of operations (overall survival [OS], p = 0.82; progression-free survival [PS], p = 0.41) and the order of surgery and chemotherapy treatment (OS, p = 0.85; PS, p = 0.83) did not significantly impact the outcomes. Further, MM patients with surgery exhibited a significant prognostic difference compared to those without surgery (OS, p < 0.0001). The International Staging System (ISS) stage serves as a prognostic factor for MMBD who have undergone surgery, with higher ISS stages indicating worse prognoses.ConclusionsThese results indicate that surgery and chemotherapy together improved patient survival rates compared to chemotherapy alone, thereby facilitating patients' acceptance of systemic chemotherapy. Furthermore, the appropriate timing of surgery contributes to the positive prognoses of patients with MMBD.